PERAN OBLIGASI SYARIAH (SUKUK) BAGI INVESTOR - NURYANTI NURYANTI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
Syariah bonds (sukuk) are Government Securities issued under sharia principles as proof of participation in State Sharia Securities (SBSN) assets in both rupiah and foreign currency. Where the issuer is obliged to pay revenues in the form of returns to investors and return principal on maturity. This means that bonds with a maturity of five years, sukuk holders receive a yield every month and principal funds are returned at maturity. The role of sharia bonds for investors is this investment is guaranteed payment by the government, for sharia investors this investment is not contrary to the principles of sharia, so in addition to safe also reassuring. In addition, the benefits earned are more profitable than the average deposit rate of BUMN Banks, potentially acquiring Capital Gains, can be marketed in the secondary market through the Stock Exchange, and provide an opportunity for the community to participate in supporting the financing of national development. Sukuk Investment Fund at least five million rupiah per multiplier and maximum five billion. The funds are used to finance infrastructure development. For example for the construction of highways, the purchase of assets in the form of buildings, buildings leased to audiences, then the results of rental buildings provided by investors as the yield of sukuk. The party managing the fund is the issuer or issuer, the return is directly debited in investor's account every month.